The Role Of Economic Growth : The Effect Of Regional General Income And Balancing Fund On Capital Expenditure - Carissa Endarto, Laurenthia; Ekaningtias, Diah (IQTISHADequity jurnal MANAJEMEN, 2024)
This study uses the dependent variable, namely capital expenditure calculated by expenditure on land, equipment and machinery, buildings and buildings, roads, irrigation, networks, and other fixed assets and the independent variable is the original opinion of the region and the balancing fund measured using the amount of each district government in East Java Province. With the population of all districts registered with the Central Statistics Agency (BPS) with a sample of 29 districts for the 2019-2022 period. Sampling is carried out by purposive sampling method, where samples are selected based on criteria made by researchers. Data were analyzed by descriptive analysis techniques, classical assumption tests and Moderated Regression Analysis (MRA) using SPSS 26. The results of this study show that regional general income affects capital expenditure, balancing funds affect capital expenditure, while with economic growth, regional original income has no effect and balancing funds affect capital expenditure.